A new prescription for the spectral properties of population III stellar populations - Lecroq, Marie; Charlot, Stéphane; Bressan, Alessandro; Bruzual, Gustavo; Costa, Guglielmo; Iorio, Giuliano; Mapelli, Michela; Santoliquido, Filippo; Shepherd, Kendall; Spera, Mario (Astronomy and astrophysics, 2025)
We investigated various emission properties of extremely low metallicity stellar populations in the Epoch of Reionization (EoR), using the new GALSEVN model, which has shown promising agreement between spectral predictions and observations at lower redshifts and higher metallicities. We find that emission-line diagnostics previously proposed to discriminate between population III (Pop III) stars and other primordial ionizing sources are effective, but only for stellar-population ages below ∼1 Myr. We provide other key quantities relevant to modeling Pop III stellar populations in the EoR, such as the production efficiency of ionizing photons, which is critical for reionization studies, the production rate of Lyman-Werner photons, which can dissociate H2 and influence the efficiency of star formation, and the rates of different types of supernovæ, offering insights into the timescales of chemical enrichment in metal-poor environments. We complement our study with a self-consistent investigation of the gravitational-wave signals generated by the mergers of binary black holes that formed through stellar evolution and their detectability. The results presented here provide valuable predictions for the study of the EoR, on the crucial role of low-metallicity stellar populations in reionization mechanisms and star formation, as well as meaningful insights into potential observational counterparts to direct detections of Pop III stars.